A MicroRNA-BDNF Negative Feedback Signaling Loop in Brain: Implications for Alzheimer’s Disease - Keifer, Joyce; Zheng, Zhaoqing; Ambigapathy, Ganesh (MicroRNA, 2015)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression posttranscriptionally by interfering with translation of their target mRNAs. Typically, miRNAs bind to the 3’ UTRs of mRNAs to induce repression or degradation. Neurotrophins are growth factors in brain required for neuronal survival, synapse formation, and plasticity mechanisms. Neurotrophins are not only regulated by miRNAs, but they in turn regulate miRNA expression. Accumulating data indicate there is a regulatory negative feedback loop between one ubiquitous neurotrophin, brain-derived neurotrophic factor (BDNF), and miRNAs. That is, while BDNF treatment stimulates neuronal miRNA expression, miRNAs generally function to inhibit expression of BDNF. This negative feedback loop is maintained in a state of equilibrium in normal cells. However, in Alzheimer’s Disease (AD), a progressive neurodegenerative disorder resulting in memory loss and eventually dementia that is characterized by reduced levels of BDNF in brain, the balance between BDNF and miRNA is shifted toward inhibitory control by miRNAs. Here, we will briefly review the evidence for a positive action of BDNF on miRNA expression and a negative action of miRNAs on BDNF. We propose that the reduction in BDNF that occurs in the AD brain is the result of two independent mechanisms: 1) a failure in the proteolytic conversion of BDNF precursor protein to its functional mature form, and 2) inhibition of BDNF gene expression by miRNAs. The role of miRNAs in BDNF regulation should be considered when developing BDNF-based therapeutic treatments for AD.
Keywords: neurotrophins